Formation of Methane versus Benzene in the Reactions of (C5Me5)2Th(CH3)2 with [CH3PPh3]X (X=Cl, Br, I) Yielding Thorium‐Carbene or Thorium‐Ylide Complexes. Issue 42 (7th September 2017) - Rungthanaphatsophon, Pokpong; Bathelier, Adrien; Castro, Ludovic; Behrle, Andrew C.; Barnes, Charles L.; Maron, Laurent; Walensky, Justin R.
Abstract: The reaction of (C5 Me5 )2 Th(CH3 )2 with the phosphonium salts [CH3 PPh3 ]X (X=Cl, Br, I) was investigated. When X=Br and I, two equivalents of methane are liberated to afford (C5 Me5 )2 Th[CHPPh3 ]X, rare terminal phosphorano‐stabilized carbenes with thorium. These complexes feature the shortest thorium–carbon bonds (≈2.30 Å) reported to date, and electronic structure calculations show some degree of multiple bonding. However, when X=Cl, only one equivalent of methane is lost with concomitant formation of benzene from an unstable phosphorus(V) intermediate, yielding (C5 Me5 )2 Th[κ 2 ‐(C, C′)‐(CH2 )(CH2 )PPh2 ]Cl. Density functional theory (DFT) investigations of the reaction energy profiles for [CH3 PPh3 ]X, X=Cl and I showed that in the case of iodide, thermodynamics prevents the production of benzene and favors formation of the carbene. Abstract : Picky thorium : Reaction of (C5 Me5 )2 Th(CH3 )2 with the phosphonium salts [CH3 PPh3 ]X affords terminal thorium‐carbene complexes when X=Br and I, showing thorium–carbon multiple bonding. When X=Cl, a thorium‐ylide complex is formed.